Pastabos dėl žemaičių trumpinių kilmės pavardžių, kilusių iš avd. Gedrìmas - Sinkevičiūtė, Daiva (Baltistica, 2009)
OBSERVATIONS ON ŽEMAITIAN SHORTENED SURNAMES DERIVED FROM THE PROPER NAME Gedrìmas Beside the Lithuanian proper name Gedrìmas and its shortened derivatives in Gedr- we also frequently find Giedrìmas, Giedr-. The variant Giedr- was probably due to the influence from documents written in Polish, where Gedr- was regularly written Giedr-. The variant Gedr- is particularly well attested in Žemaitian area (where Giedr- in any case also occurs) where it was not changed to Giedr- because there was no possible secondary association with the adjective gydras, the form used in most of Žemaitian area instead of (Aukštaitian) giẽdras.